HISTORICAL-ETYMOLOGY AND LINGUISTICAL ANALYSIS OF THE NAMES OF MEDICINAL PLANTS IN UZBEKI AND ENGLISH LANGUAGES - Rakhimova Nigora Polvonnazirovna (Journals Park Publishing, 2024)
Researchers have always been interested in the names of medicinal plants in Uzbek and English languages. This topic is becoming interesting and relevant for translators. In this article, we considered the historical-etymological and linguostatistical analysis of medicinal plant names in Uzbek and English.
Keywords: names of medicinal plants, origin, semantics, linguistic statistics, Latin language, English language, Uzbek language.